Slovene: Skripta pri predmetu Temelji finančnega inženiringa - Marovt, Janko (University of Maribor Press, 2021)
Options, Forwards, Futures, and the Binomal Tree Model: Material for the course Fundamentals of Financial Engineering. The script "Options, forwards, futures, and the binomial tree model" is intended for the students of the course Fundamentals of financial engineering which is conducted at the Faculty of Natural Sciences and Mathematics. It presents basic concepts of financial engineering. The assumptions on which most of mathematical models that simulate the financial markets are first given. Proofs of propositions and theorems are based on the principle of no-arbitrage. Some derivative financial instruments are presented. In the central part of the script, forward and futures contracts are first analyzed. The binomial tree model is next presented. This model is then used in the evaluation of European and American call and put options. The script is equipped with many solved examples.